A New Class of Organic Crystals with Extremely Large Hyperpolarizability: Efficient THz Wave Generation with Wide Flat‐Spectral‐Band. (31st October 2022) - Kim, Seung‐Jun; Yu, In Cheol; Kim, Dong‐Joo; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract: In organic π‐conjugated crystals, enhancing molecular optical nonlinearity of chromophores (e.g., first hyperpolarizability β ≥ 300 × 10 −30 esu) in most cases unfortunately results in zero macroscopic optical nonlinearity, which is a bottleneck in organic nonlinear optics. In this study, a new class of nonlinear optical organic crystals introducing a chromophore possessing an extremely large first hyperpolarizability is reported. With newly designed 4‐(4‐(4‐(hydroxymethyl)piperidin‐1‐yl)styryl)‐1‐(pyrimidin‐2‐yl)pyridin‐1‐ium (PMPR) chromophore, incorporating a head‐to‐tail cation‐anion OH⋯O hydrogen‐bonding synthon and an optimal selection of molecular anion into crystals results in extremely large macroscopic optical nonlinearity with effective first hyperpolarizability β iii eff β _iii^eff of 335 × 10 −30 esu. This is in sharp contrast to zero β iii eff β _iii^eff value for previously reported analogous crystals. An ultrathin PMPR crystal with a thickness of ≈10 µm exhibits excellent terahertz (THz) wave generation performance. Both i) broadband THz wave generation with a wide flat‐spectral‐band in the range of 0.7–3.4 THz defined at −3 dB and high upper cut‐off generation frequency of > 7 THz as well as ii) high‐generation efficiency (5 times higher THz amplitude than ZnTe crystal with a mm‐scale thickness) are simultaneously achieved. Therefore, new PMPR crystals are highly promising materials for diverse applications in nonlinear optics and THz photonics. Abstract : Newly designed 4‐(4‐(4‐(hydroxymethyl)piperidin‐1‐yl)styryl)‐1‐(pyrimidin‐2‐yl)pyridin‐1‐ium crystals possessing extremely large macroscopic optical nonlinearity (335 × 10 −30 esu) exhibit broadband THz wave generation with a wide flat‐spectral‐band in the range of 0.7–3.4 THz together with a high‐generation efficiency.